Synthesis and spectral studies of complexes between palladium and some thiosemicarbazones - Chau et al, Trinh Ngoc (Vietnam Journal of Chemistry, 2014)
This paper reviews the synthesis and spectral studies of some complexes of palladium with thiosemicarbazones: Pd(L1)NH3 (L1: pyruvic acid thiosemicarbazone) and Pd(Li)2), (i: 2-4, thiosemicarbazone of: acetophenone (L2), benzaldehyde (L3), p-dimethylaminobenzaldehyde(L4)). The ligands and complexes are characterized by means of chemical analysis, thermal analysis, IR, ESI-MS and 1H-NMR spectroscopy. The obtained data show that in Pd(L1)NH3, three coordinate sites are realized by S, N(1) and O-atoms of  L1 and the fourth coordinate site  by NH3-group; in Pd(Li)2) complexes, Li acts as anionic bidentate ligands, two coordinate bonds realize through S and N(1) atoms. Especially, the obtained data 1H-NMR spectrum of Pd(L2)2 indicate that this complex exists in two isomers, supposed to be cis and trans, in DMSO solutions.